Biochemical Characterization Of The Interaction Between CTCF/YB-1 Transcription Factors With HPV 16 And 18 E7 Oncoprotein And Their Involvement During C-MYC Gene Regulation In Cell Proliferation Pathway [QR406. V471 2008 f rb]. - Balakrishnan, Venugopal (2008)
Human Papillomaviruses (HPVs) type HPV-16 and HPV-18 are known as high risk HPV, which are cause 95% of cervix cancer.